PEMBELAJARAN BAHASA ARAB BERBASIS MEDIA SOSIAL UNTUK MENAMBAH HAFALAN KOSA KATA SISWA MI - Lailatul Maghfiroh (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the use of social media in Arabic language learning at Madrasah Ibtidaiyah (MI), focusing on the enhancement of students' vocabulary memorization. Social media-based learning offers a more interactive and flexible approach, utilizing platforms like Instagram, YouTube, and WhatsApp to enrich students' learning experiences. The findings indicate that the use of social media can increase motivation, engagement, and understanding of Arabic vocabulary. However, there are technical and non-technical challenges to be addressed, such as internet access limitations and the potential for distractions. Therefore, careful management is needed to ensure social media is utilized optimally in Arabic language learning.